EFFECTIVENESS OF PANDAN WANGI LEAF EXTRACT (Pandanus amaryllifolius Roxb.) ON NUMBERS DEATH OF LARVA Aedes aegypti - Homamah, Patim; Setyo Budi Susanto; Mayta Sari Dwianggimawati (Universitas STRADA Indonesia, 2019)
Increased cases of dengue hemorrhagic fever accompanied by the emergence of resistance to temephos, making the use of natural larvicides begin to be considered. One of the natural ingredients that can be used is the fragrant pandan leaves (Pandanus amaryllifolius Roxb). The purpose of this study was to examine the concentration and effectiveness of Pandanus leaf extract (Pandanus amaryllifolius Roxb.) To kill Aedes aegypti larvae. This research is an experimental research with posttest only control group design where the object is divided into two groups: the control group and the treatment group. Samples were 25 larvae in each group, and it was repeated four times. So the total sample is 800 Aedes aegypti larvae. The results of this study indicate that at a concentration of 0% (negative control) aquades can kill 0 Aedes aegypti larvae, at a concentration of 1% (positive control) can kill an average of 56%, a concentration of 0.5% can kill 16.75 (17) larvae (67%), a concentration of 0.7% can kill 18.75 (19) larvae (75%), a concentration of 0.9% can kill 20.5 (21) larvae (82%), a concentration of 1.0% can kills 22.25 (23) larvae (89%), a concentration of 3.0% can kill 24 larvae (96%), and a concentration of 5.0% can kill 25 larvae (100%). Based on the analysis of the one way ANOVA test, it can be concluded that there is an effect of fragrant pandanus leaf extract on the mortality of Aedes aegypti larvae with a significant p value of 0,000 (p <0.05). Pandan (Pandanus amaryllifolius Roxb.) Fragrant pandan leaf extract (Pandanus amaryllifolius Roxb) at 5.0%concentration is the most effective concentration to kill Aedes aegypti mosquito larvae. Conclusion: Fragrant pandan leaves (Pandanus amaryllifolius Roxb) are effective in causing the death of Aedes aegyti mosquito larvae.